Socio-demographic factors associated with retention of female sex workers in healthcare in Hillbrow and Pretoria sex worker clinics - Bothma, Rutendo (My University, 2020)
Introduction: Female sex workers (FSWs) have increased vulnerabilities to violence, STIs and HIV infection, which are often exacerbated by the social conditions of their occupation. Furthermore, there are political, social and structural factors that hinder their utilisation and retention in healthcare. The aim of this study was to understand how FSWs in two South African urban settings (Johannesburg and Pretoria) remained in care over a five-year period, and factors which shaped these patterns of retention. Methods: This was a retrospective cohort study. It utilised secondary analysis of routine data collected on sex workers in the Wits Reproductive Health and HIV Institute (Wits RHI) sex worker programme. The study population was FSWs who were of any nationality and 18 years or older. Descriptive statistics were conducted to describe the study setting, profile of the FSWs and levels of retention. Retention was defined as having more than one clinic visit during the study period, 2013 to 2017. Bivariate analysis was performed to determine crude associations between socio-demographic and other factors and the dependent variable, retention. A multivariate logistic regression model was fitted to detect independent associations between the retention and the independent variables. Results: Data was available for 7 624 FSWs, (5 737; 79%) accessed services in Johannesburg and (1 546, 21%) accessed services in Pretoria. The average age of FSWs accessing Wits RHI services was 29 years, with a standard deviation (SD) of 6.5. A quarter of them were between 18-24 years old. Retention in care was low, with only over a third (37%) of all FSWs accessing the clinic more than once within the study period. Independent variables that influenced retention included older age (AOR: 1.48, 95% CI: 1.13-1.93), accessing services in Pretoria (AOR: 1.78, 95% CI: 1.45-2.19), accessing services at a fixed clinic (AOR:0.70, 95% CI: 0.59-0.85), and Zimbabwe as country of birth (AOR: 1.31, 95% CI: 1.07-1.51). Conclusion: The low retention reported in this study highlights the need for creating an enabling environment that encourages FSWs to be continuously engaged in health care when they need services. The high proportion of young, new and foreign FSWs indicates the importance of designing programmes that are acceptable and prioritise the different needs of FSWs. The data analysed in this study indicate the need for a combination package of services to provide interventions that address biological, social, and structural determinants of poor health, tailored to the priorities, and needs of this group. Overall, the findings from this study contribute to the knowledge of factors that drive retention and the gaps programmes can address to keep FSWs engaged in healthcare services.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Public Health in the field of Health Systems and Policy to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020